Pengaruh Kompres Hangat Terhadap Penurunan Derajat Nyeri Haid Pada Remaja Putri - Purwanti, Erna (POLTEKKES KEMENKES MANADO, 2024)
Background: Complaints during menstruation include menstrual pain disorders caused by excessive myometrial muscle contractions which reduce blood flow, resulting in a lack of oxygen in the myometrium cells which results in pain during menstruation. Objective: this research is to examine and review several literature related to warm compresses for menstrual pain in teenage girls. Method: This type of research is qualitative with a literature study approach review. Resources used in the search database electronics are Google Scholar, PubMed, and Indonesia One Search with keywords tailored to the required title. Articles used to support research are before 2024. Results: Literature analysis explains that warm compresses are a safe intervention and non-pharmacological alternative therapy that can be used to reduce menstrual pain in young women.